(3CSGSjGJ GdESJKeGQs - (3WGgQ MjOQ(B, (3MQOGfs ((3YeGf(B:s (3OGQ GdeSJbHd(B,s, 2008)
(3ebOeI aj GdGSJKeGQ h CShGb h eDSSGJ GdGSJKeGQ , CQcGf h CSGdjH GdJYGed aj CShGb GdGSJKeGQ GdeGdj , SYQ GdaFOI h GdGSJKeGQ , Jchjf GdeMGaX GdGSJKeGQjI h JMdjdgG h JYOjdgG h GdeHGOdI Hjf GdeNGWQI h GdYGFO , GdGSJKeGQ HGdGSge h GdSfOGJ , CSS Jbjje GdGhQGb GdeGdjI h GdgOa ef gPG GdJbjje , GdJYGed HCOhGJ GdGSJKeGQ aj GdShb GdfbOjI ,CSGdjH GdeaGVdI Hjf ChLg GdGSJKeGQ (B.s
(3eQGLY U(B.199 (3; edGMb U (B183s
Keywords: (3GdCShGb GdeGdjIs; (3GdESJKeGQs; (3GdSfOGJs